2001
DOI: 10.2105/ajph.91.7.1082
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of invasive procedures among Medicaid patients with acute myocardial infarction

Abstract: OBJECTIVES: The purpose of this study was to determine whether underuse of cardiac procedures among Medicaid patients with acute myocardial infarction is explained by or is independent of fundamental differences in age, race, or sex distribution; income, coexistent illness; or location of care. METHODS: Administrative data from 226 hospitals in New York were examined for 11,579 individuals hospitalized with a primary diagnosis of acute myocardial infarction. Use of various cardiac procedures was compared among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Both these medical conditions are of course strongly related to presence of diabetes [ 22 ] and indeed were among the strongest independent predictors of DM diagnosis in our study. Other factors independently linking co-existent DM with incident AMI in our multivariable analyses were female sex, non-White race, and comorbid systemic vascular damage have been noted in other studies [ 23 26 ].…”
Section: Discussionsupporting
confidence: 52%
“…Both these medical conditions are of course strongly related to presence of diabetes [ 22 ] and indeed were among the strongest independent predictors of DM diagnosis in our study. Other factors independently linking co-existent DM with incident AMI in our multivariable analyses were female sex, non-White race, and comorbid systemic vascular damage have been noted in other studies [ 23 26 ].…”
Section: Discussionsupporting
confidence: 52%
“…We selected outcomes previously shown to be influenced by insurance coverage: likelihood of admission to a hospital with PCI capacity ("PCI hospital"), [1] likelihood of transfer for patients who initially presented with AMI to hospitals without PCI capacity, [1,2] likelihood of undergoing PCI during index hospitalization, [9] early PCI defined as having received PCI within 48 hours of admission, [33] in-hospital mortality, and readmission within 30 days of discharge. [6] We defined receipt of PCI by procedure codes in the discharge record (ICD-9 codes 0.66, 17.55, 36.00, 36.04, 36.06, 36.07, 36.09), [25,[34][35][36][37] Following previous literature, we defined hospitals as PCI hospitals if they performed at least 4 PCIs per year. [38][39][40] If a patient was transferred and received PCI at the destination hospital, we considered the procedure to be performed on index hospitalization.…”
Section: Study Outcomesmentioning
confidence: 99%
“…In other words, not all types of insurance may be seen equally; as other studies have found, patients with Medicaid receive different treatment from those with commercial private insurance. [25,46] Ours is the first study that we know of to examine whether the Medicaid expansion affected readmission rates after hospitalization for AMI. The reduction in 30-day readmission rates https://doi.org/10.1371/journal.pone.0232097.g004…”
Section: Plos Onementioning
confidence: 99%
“…Hospitals that performed 4 or more PCIs per year were considered PCI hospitals [ 5 , 6 , 34 ]. Hospitals performing PCI procedures were identified in the data set using PCI procedure codes in the discharge records (ICD-9 codes 0.66, 17.55, 36.00, 36.04, 36.06, 36.07, 36.09) [ 1 , 12 , 13 , 28 , 35 ]. For a sensitivity analysis examining ST-elevation myocardial infarction (STEMI) patients separately, we identified patients with a primary discharge ICD-9 code of 410.x0, 410.x1, excluding 410.7x and 410.9x, as patients with STEMI.…”
Section: Methodsmentioning
confidence: 99%